2011
DOI: 10.1007/s00018-011-0782-7
|View full text |Cite
|
Sign up to set email alerts
|

Roles for CCN2 in normal physiological processes

Abstract: CCN2, also known as connective tissue growth factor, is a member of the CCN (CCN1-6) family of modular matricellular proteins. Analysis of CCN2 function in vivo has focused primarily on its key role as a mediator of excess ECM synthesis in multiple fibrotic diseases. However, CCN2 and related family members are widely expressed during development. Recent studies using new genetic models are revealing that CCN2 has essential roles in the development of many tissues. This review focuses on current and emerging d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
83
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(88 citation statements)
references
References 74 publications
2
83
0
Order By: Relevance
“…From early disc development to maturation, many studies have reported an anabolic effect of CCN2 in maintaining the matrix components of the disc (Chiou et al, 2006;Hall-Glenn and Lyons, 2011;Huang et al, 2010;Tran et al, 2013a;Tran et al, 2013b;Tran et al, 2011). In the degenerative disc, several recent studies have demonstrated a positive correlation between CCN2 levels and the severity of degeneration (Tran et al, 2010) and the presence of pain (Peng et al, 2009).…”
Section: Different Molecular Signals and Interactions In Normal Intermentioning
confidence: 99%
“…From early disc development to maturation, many studies have reported an anabolic effect of CCN2 in maintaining the matrix components of the disc (Chiou et al, 2006;Hall-Glenn and Lyons, 2011;Huang et al, 2010;Tran et al, 2013a;Tran et al, 2013b;Tran et al, 2011). In the degenerative disc, several recent studies have demonstrated a positive correlation between CCN2 levels and the severity of degeneration (Tran et al, 2010) and the presence of pain (Peng et al, 2009).…”
Section: Different Molecular Signals and Interactions In Normal Intermentioning
confidence: 99%
“…Connective tissue growth factor (CTGF, CCN2) belongs to the CCN (an acronym of Cyr61/CEF-10, CTGF/Fisp-12, Nov) family of immediate early genes, which are highly conserved among different species. Studies have shown that CTGF has essential roles in the development of normal tissues, such as follicle, ovulation [2], chondrogenesis, cartilage [3], alveolarization during lung maturation [4], and angiogenesis [5]. In addition, CTGF has crucial roles in epithelial tissues [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Sustained hyperglycemia can promote the release of some cytokines and growth factors such as connective tissue growth factor (CTGF) and epidermal growth factor-β (TGF-β) [14]. The massive relaxation of CTGF in the course of long-term diabetes will cause a huge expression of extracellular matrix(ECM) [15][16], which can promote cell hypertrophy and interstitial fibrosis, leading to the change of cardiac functions. Even more, TGF-β can also induce cell hypertrophy and mesangial matrix expansion through a series signaling reactions with receptors [17].…”
Section: Introductionmentioning
confidence: 99%